Double drainage of total anomalous pulmonary venous connection revealed after surgical repair of a supracardiac total anomalous pulmonary venous connection - Hiroyuki Nagao; Kenta Tominaga; Naoya Kamei; Toshikatsu Tanaka (Clinical Case Reports, 2020)
Abstract Mixed type TAPVC with double drainage, where the second vertical vein enlarged rather than atrophied after surgery. If we did not recognize left‐to‐right shunting before surgery, it can be treated with catheterization as demonstrated by our case.